SECONDARY HYPERTROPHIC OSTEOARTHROPATHY (PIERRE MARIE–BAMBERGER SYNDROME) - A. S. Krylov; Ya. A. Shchipakhina; A. V. Fedorova; S. V. Shiryaev; A. D. Ryzhkov; N. V. Kochergina; M. O. Goncharov; A. S. Nered; A. B. Bludov (Вестник рентгенологии и радиологии)
This article describes a clinical case of a cancer patient with secondary hypertrophic osteoarthropathy (Pierre Marie–Bamberger syndrome). The patient underwent complex examination including bone scan, X-ray, computed tomography and magnetic resonance imaging. According to the results of the examinations the patient was diagnosed with metastatic amelanotic melanoma in intrathoracic lymph nodes with unknown primary site and the Pierre Marie–Bamberger syndrome was confirmed.